The postman has arrived - Miguel , Kelly Cristina Pádua Bruzegueze; Salmazo , Gabriela de Andrade Junqueira; Figueiredo, Juliana Nascimento; Ferreira, Pâmela Virgínia Nascimento (Seven Editora, 2023)
The present work corresponds to an account of a pedagogical practice developed in three rooms of Early Childhood Education, phase II of the Samarian Institute of Teaching, Franca/SP. The responsible teachers described the activities performed and the reaction of the children to each stage of the project. The objective of the work was to reflect on the events of each story presented in the book and weave the idea of complexity when interconnecting the tales. By working literature with young children, one contributes to the formation of critical citizens and aware of their attitudes in society. The project was elaborated from the book "The Postman Has Arrived". Because it is a charming text, it stimulates the children's imagination and invites the reader to reflect on the attitudes of the characters of the different stories presented. We were able to provide moments of significant experiences based on pedagogical practices committed to the integral formation of children. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-014